Methodological Work Performed by Education Libraries of the MES of Ukraine and the NAES of Ukraine: Publishing Reflection - Ruban Alla (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2019)

(untitled)
In order to study 2013-2017 methodological production prepared by the leading education libraries, the author of the paper analyzed their web-sites and publications available in the holdings of V. O. Sukhomlynskyi SSPL of Ukraine and used the information given in Leading education libraries in space and time: monitoring of their activity reference book for the mention period. The analysis showed that education library publishing is a diverse and many-sided activity. E-publications (both electronic ones and those that have a paper version) constitute a significant part of their publishing. It was found out that the following various methodological publications were issued by education libraries: practical, teaching, reference, review, research, information, serial, normative, and instructive publications. In addition, librarians write papers for periodicals and serials. It was established that education library publishing for the analyzed period was aimed at popularizing the best practices, developing and introducing innovation process and technique. It was mentioned that the most popular subject matters of publications were as follows: library information resources (formation and access to them), library publishing, and methodological support for observing anniversary and memorable dates.